"Oh, S**t! Did i just swear in class?": Using emotional response theory to understand the role of instructor swearing in the college classroom. Issue 2 (15th March 2019) - Generous, Mark A.; Houser, Marian L.
Abstract : The current study examines students' emotional responses to instructor swearing and extends previous research to validate functions and targets of instructor swearing. A measure was created to assess college students' perceptions of instructor swearing. A principle components analysis yielded a seven-factor structure that supports past functions and targets of classroom swearing: at self/job tools; at students/assignments; to elaborate course concepts; part of the instructor's disposition; to gain attention; accidental swearing; and, to converge/be humorous. Framed by emotional response theory (ERT), instructor swearing behaviors significantly predicted students' pleasure and dominance emotions. Additionally, students' emotional responses in the classroom explained significantly more unique variation in students' cognitive and affective learning, and motivation, compared to instructor swearing. Implications for instructional practice and instructional communication theory are addressed.